(untitled) (KULT_online, 2019)
Literary Journalism is a popular topos within media studies. Michael Homberg’s dissertation Reporter-Streifzüge: Metropolitane Nachrichtenkultur und die Wahrnehmung der Welt now equips the term with a comparative genesis that is characterized by the history of the reportage. For Homberg, the metropolis, the local, and the global are pivotal points in this amalgamation of fact and fiction in the reportage. His research is particularly convincing due to a broad selection of case studies and the highlighting of self-referential media societies.